Upgrade of the CMS Barrel Electromagnetic Calorimeter for the LHC Phase-2 - Orlandi Francesco (EPJ Web of Conferences)
The Phase-2 High-Luminosity upgrade of the LHC (HL-LHC) at CERN will provide from 2029 onwards an unprecedented instantaneous and integrated luminosity of around 5 1034cm−2s−1 and 3000 fb−1, respectively. Particular challenges at the HL-LHC are the harsh radiation environment, the increasing data rates, and the extreme level of pileup events, with up to 200 simultaneous proton-proton collisions expected. In the barrel region of the CMS electromagnetic calorimeter (ECAL), the lead tungstate crystals and avalanche photo-diodes (APDs) will continue to function and meet the Phase-2 requirements, while the readout and trigger electronics need to be replaced. The upgraded on-detector readout will use new, faster analog electronics and an increased pulse sampling rate to provide better time resolution, which will improve pileup mitigation and the rejection of large unwanted signals in the APDs, termed spikes. This paper provides an overview of the scope of the ECAL barrel upgrade, describes the current status, and highlights the key results from the latest integration tests.